Relationship Between Emotional Labor and Mental Health in Preschool Teachers: Mediation of Psychological Capital - Hong, Yao; Huang, Jian-Hao; Zhang, Jiping (Frontiers in Psychology, 2022)
This study explored the relationship among the emotional labor, psychological capital and mental health of preschool teachers. A questionnaire survey was conducted on 411 preschool teachers in China. The results revealed the following: (1) One emotional labor strategy (Surface acting) had a significant negative effect on mental health, whereas two emotional labor strategies (Expression of naturally felt emotions and Deep acting) had significant positive effects. (2) The psychological capital of preschool teachers had a complete mediation on the relationship between expression of naturally felt emotions and mental health and between the deep acting and mental health.